A Model of Leadership Development on Application of Technologies for Police Cadets in Accordance with Thailand 4.0 Policy - ทองมุณี , ปกรณ์ (Academic Journal of North Bangkok University, 2020)
The purpose of this study was to develop a model of leadership development on application of technologies for police cadets in accordance with Thailand 4.0 policy. The research was conducted in 3 steps which are: Step 1: To study documents and interview police technology experts in accordance with Thailand 4.0 policy in order to obtain by applying and synthesizing the knowledge necessary for the development of technology leadership in the era of Thailand 4.0. Step 2: To create a model to develop leadership in the application of technology of the police cadets in accordance with Thailand 4.0 policy, which has been drafted by short-term training. Checked by 5 experts. Step 3: Trial using the developed model with 161 3rd year police cadets. The tools used for collecting data were the police leadership development program in technology application of the police cadets in accordance with the Thailand 4.0 policy, and the evaluation form of the developed model. The statistics used for data analysis are percentage, average, and Standard Deviation. Research findings reveal that the developed model is appropriate and feasible to use. Also, after joining the program, it was found that the police cadets had evaluated the leadership development model on application of technologies in accordance with Thailand 4.0 in all 3 areas: knowledge, skills, and attitude at a high to the highest level.